Detrimental Effects Of Capacitance On High-Resistance-Grounded Mine Distribution Systems - Joseph Sottile; Steve J. Gnapragasam; Thomas Novak; Jeffrey L. Kohler (The National Institute for Occupational Safety and Health (NIOSH))
Modern underground coal mines can be very large, having a total connected load in excess of l5 000 hp. These mines generally have many miles of high-power conveyor belts and 15 or more miles of high-voltage power cables at distribution voltages of 12.47, 13.2, 13.8, or 14.4 kV. The shielded cables used in mine power distribution systems have a significant level of capacitance, on the order of 110 pF/ft. This level of capacitance, in an extensive power distribution system at today's voltage levels, can cause significant charging currents during a ground fault. This paper addresses the potential detrimental effects of capacitance charging currents during line-to-ground faults in mine power distribution systems. A representative mine power system is modeled, and simulations with faults at various locations are conducted to evaluate the effects of this capacitance on the level of fault current and relay selectivity. This paper also includes results of capacitance measurements made on mine power feeder cables used to validate the simulation model.